Prospective randomized comparative study of the effect of pemafibrate add‐on or double statin dose on small dense low‐density lipoprotein‐cholesterol in patients with type 2 diabetes and hypertriglyceridemia on statin therapy - Tsutomu Hirano; Toshiyuki Hayashi; Hiroe Sugita; Atsuko Tamasawa; Satoshi Goto; Masako Tomoyasu; Takeshi Yamamoto; Makoto Ohara; Michishige Terasaki; Hideki Kushima; Yasuki Ito; Sho‐ichi Yamagishi; et al. (Journal of Diabetes Investigation, 2023)
Abstract Aims/Introduction Small dense low‐density lipoprotein (sdLDL) is a more potent atherogenic lipoprotein than LDL. As sdLDL‐cholesterol (C) levels are determined by triglyceride and LDL‐C levels, pemafibrate and statins can reduce sdLDL‐C levels. However, it remains unclear whether adding pemafibrate or increasing statin doses would more effectively reduce sdLDL‐C levels in patients receiving statin therapy. Materials and Methods A total of 97 patients with type 2 diabetes and hypertriglyceridemia who were treated with statins were randomly assigned to the pemafibrate 0.2 mg/day addition or statin dose doubled, and followed for 12 weeks. sdLDL‐C was measured by our established homogenous assay. Results The percentage and absolute reductions of sdLDL‐C levels were significantly greater in the pemafibrate add‐on group than the statin doubling group (−32.8 vs −8.1%; −16 vs −3 mg/dL, respectively). Triglyceride levels were reduced only in the pemafibrate add‐on group (−44%), and LDL‐C levels were reduced only in the statin doubling group (−8%), whereas levels of non‐high‐density lipoprotein‐C and apolipoprotein B were similarly decreased (7–9%) in both groups. The absolute reductions of sdLDL‐C levels were closely associated with decreased triglyceride, LDL‐C, non‐high‐density lipoprotein‐C and apolipoprotein B. In the subgroup analysis, the effect of pemafibrate add‐on on sdLDL‐C reductions was observed irrespective of baseline lipid parameters or statin type. No serious adverse effects were observed in both groups. Conclusions In patients with type 2 diabetes and hypertriglyceridemia, the addition of pemafibrate to a statin is superior to doubling a statin in reducing sdLDL‐C without increasing adverse effects.